Bonds or Conflicts? Religious Organizations in the Evolving Global Order - Simai, Mihály (Religious studies and theology, 2010)
In spite of the global process of secularization, religion has remained important in the lives of people, countries and also in international relations. This article discusses the role of organized religion and communities of believers in shaping world orders and influencing their function. It reveals that religious organizations, particularly those with thousand of years of traditions, are not only different expressions of human beings in their relations to a spiritual world, but also a complex global network with varying influence on different societies. However, given its long history of strained and often confrontational relationships with the secular world, the contemporary role of religious denominations begs a fundamental question. Will the different doctrines, social teaching and norms promote progress toward "globalization with a human face" or will they simply aggravate global division and confrontations in an already divided world?